EVALUATION OF THE FINANCIAL PERFORMANCE OF THE CITY GOVERNMENT TANGERANG USING THE VALUE FOR MONEY METHOD FOR THE PERIOD 2014-2016 - Aisyah Margaretta (International Journal Management and Economic, 2024)
Accountability is not just the ability to show how public money has been spent, but includes the ability to show that public money has been spent economically, efficiently and effectively through good implementation. This study aims to evaluate financial performance of the Tangerang City Government using the Value for Money method for the period 2014-2016. This research method uses quantitative analysis techniques and using the Value for Money method. The results showed that the economic ratio of the financial performance of the Tangerang City Government financial performance of the Tangerang City Government is included in the economic category because the Tangerang City Government was able to make the expenditure realization always less than the budget budget set. The efficiency ratio of the financial performance of the Tangerang City Government during period 2014-2016 is already included in the efficient category, but the efficiency ratio of the Tangerang City Government has been decreasing for 3 years. The efficiency ratio of the Tangerang City Government has been decreasing for 3 years. Effectiveness ratio financial performance of the Tangerang City Government during the period 2014-2016 was categorized as effective, even exceeding the revenue budget target that had been determined. It can be concluded that the financial performance of the Tangerang City Government Tangerang City Government for the period 2014-2016 has been running well based on the concept of Value for Money. Value For Money concept.